Storm wave runups and sea level variations for the September 2017 Hurricane Maria along the coast of Dominica, eastern Caribbean sea: evidence from field surveys and sea-level data analysis. Issue 3 (3rd July 2018) - Heidarzadeh, Mohammad; Teeuw, Richard; Day, Simon; Solana, Carmen
ABSTRACT: Dominica, along with several other Caribbean islands, was severely damaged by category-5 Hurricane Maria in September 2017. The hurricane left 68 people dead or missing, marking Maria as the worst natural catastrophe to hit this small island nation. Here, we report the results of our coastal runup field survey in February 2018 and of tide gauge sea-level data analysis. Analysis of tide gauge records shows that the duration of Maria's surge varied between 2.1 and 2.6 days in the Caribbean region and was 2.1 days at Marigot, Dominica. The surge amplitude was 75 cm in Marigot, which indicates that the size of the surge was small for a category-5 hurricane. The measured field survey runups were from 1.0 to 3.7 m, with the maximum runup at Scotts Head on the southern tip of Dominica. The largest measured runups were concentrated along the west coast of the southern half of the island and consistently decreased northwards. We attribute the observed damage to coastal structures to four mechanisms: surge/wave erosion; surge/wave forces/impacts; debris impacts to coastal structures involving in particular floating tree debris brought to the sea by river floods associated with Hurricane Maria; and intense coastal sedimentation, involving sediment brought to the sea by river floods. A flowchart of the hurricane-driven damage mechanisms is presented which provides the propagating sequence, or cascade, of events that contributed to damage and emphasizes the interactions between different processes in the hurricane.